Practice of Cash on Delivery (COD) Payment Rounding In ‘Urf Perspective (Case Study on Students of Sharia Economic Law Department, The State Islamic University Maulana Malik Ibrahim Malang) - Sari Rahma Putri; Mahbub Ainur Rofiq (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Cash on Delivery is payment system made in cash when the product has arrived to the buyer's place. In practice,there’s a custom where couriers rounding COD payments with large enough nominal without prior confirmation to the buyer. This research aims to analyze the practice of rounding COD payments based on ‘urf perspective and provide alternative solutions to avoid disputes because rounding done by couriers. This research includes empirical legal research using legal and conceptual approach. The research subjects are active students of HES UIN Malang 2018. Then data collection method using questionnaires, interviews, and documentation. The results show that there are two typologies of couriers in rounding COD payments. The first is courier who confirms the buyer to complete payment, this custom includes ‘urf ṣahih because it’s in accordance with Islamic law and Minister of Trade Regulation No.35/2013 article 6 (3&4). Then,the second typology is courier who rounds up unilaterally without confirming it first,this custom includes ‘urf fasid because there’s no element of willingness from both parties as described in QS.an-Nisa 5:29. Therefore,to avoid disputes between courier and buyer, it’s hoped that there will be good faith from both parties in order to achieve the willingness/mutual pleasure of both parties.